2016
DOI: 10.1021/acs.jchemed.6b00194
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Representational Competence with Molecular Models in Organic Chemistry

Abstract: Mastering the many different diagrammatic representations of molecules used in organic chemistry is challenging for students. This article summarizes recent research showing that manipulating 3-D molecular models can facilitate the understanding and use of these representations. Results indicate that students are more successful in translating between diagrams when they have models available, that using a model to enact the translation process in the world is predictive of learning, and that using models as fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 57 publications
0
40
0
7
Order By: Relevance
“…Research has indicated effective instructional methods to promote students’ representational competence in science, including use of concrete models (Padalkar & Hegarty, ; Stieff et al., ; Stull et al., ) or virtual models (Stull & Hegarty, ), and engaging students in construction, interpretation, or evaluation of representations (Chang et al., ; Nichols, Gillies, & Kleiss, ; Prain & Tytler, ; Zhang & Linn, ). Although the current study did not investigate how to promote students’ representational competence by interventions, the results provide insights into the nature of students’ representational competence of science including the central role of using multiple representations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated effective instructional methods to promote students’ representational competence in science, including use of concrete models (Padalkar & Hegarty, ; Stieff et al., ; Stull et al., ) or virtual models (Stull & Hegarty, ), and engaging students in construction, interpretation, or evaluation of representations (Chang et al., ; Nichols, Gillies, & Kleiss, ; Prain & Tytler, ; Zhang & Linn, ). Although the current study did not investigate how to promote students’ representational competence by interventions, the results provide insights into the nature of students’ representational competence of science including the central role of using multiple representations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Investigations of students’ representational competence in science have advanced the understanding in this field with the following findings. First, aspects of students’ representational competence in science can be improved by interventions that use concrete models (Padalkar & Hegarty, ; Stieff, Scopelitis, Lira, & Desutter, ; Stull, Gainer, Padalkar, & Hegarty, ) or virtual models (Stull & Hegarty, ), and by interventions that engage students in representational practices such as construction, interpretation, or evaluation of representations (Chang, Quintana, & Krajcik, ; Nichols, Gillies, & Hedberg, ; Prain & Tytler, ; Zhang & Linn, ).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that teachers tend to see both seeing and feeling a representation as being helpful to students to achieve a certain desired level of disciplinary understanding. Activities that employ concrete models have been shown to increase undergraduate students’ ability to translate among different representations (Stieff, Scopelitis, Lira, & Desutter, ; Stull, Gainer, Padalkar, & Hegarty, ). However, these activities were not associated with any improvement on course assessment, implying that the relationship between the use of 3D models and meaning‐making are complex.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the number of articles dealing with education of stereochemical topics has been increased in recent years. Examples include articles on methods for assigning stereochemical configurations (Eliel, 1985), representations of organic molecules (Pavlinic et al, 2001;Stull et al, 2016), rectification of difficulties concerning 3D dimensional structures, rotation and reflection use of 3D visualisation ability (Tuckey, Selvaratnam, & Bradley, 1991;Mohamed-Salah & Alain, 2016;Knowles, 2017), teaching stereochemistry with programmed instruction (Kurbanoglu, Taskesenligil & Sozbilir, 2006), web-based and student-centered stereochemistry tutorials Moore 2013 and2015), a stereogame for reviewing stereochemistry concepts (da Silva Junior et al, 2017).…”
Section: Introductionmentioning
confidence: 99%